2009
DOI: 10.1002/maco.200905355
|View full text |Cite
|
Sign up to set email alerts
|

Progress in corrosion protection as a requirement for technical progress

Abstract: In many of the more recent technologies, corrosion plays a crucial role in determining their successful application. The present paper identifies such important corrosion issues in a number of technologies, which are currently under development or have been recently discussed. In this sense, CO2 sequestration, fuel cells, offshore wind energy and other offshore technologies, geothermal energy, advanced coal conversion technologies, nuclear energy, light weight construction in transport, ionic liquids as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A general review about corrosion problems associated with the introduction of methods for the generation of renewable energies was provided in Ref. 49. Ongoing problems of corrosion and corrosion protection of OWEA were recapitulated in Ref.…”
Section: Research and Developmentmentioning
confidence: 99%
“…A general review about corrosion problems associated with the introduction of methods for the generation of renewable energies was provided in Ref. 49. Ongoing problems of corrosion and corrosion protection of OWEA were recapitulated in Ref.…”
Section: Research and Developmentmentioning
confidence: 99%
“…Structures/components that operate in humid and marine environment experience severe corrosion and undergo premature failures (Liu et al, 2016;Wen et al, 2009). In aircraft components such as battery compartments, wheel wells, landing gears and water entrapment areas, corrosion is a major concern (Cramer, 2005;Furberth and Schutze, 2009). To reduce corrosion, coatings and inhibitors are usually used (Fontana, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These alloys present high impact resistance and ductility, in addition to the ability to maintain their appearances without deterioration. Pitting corrosion is one of the most critical types of corrosion that leads to undesirable failures reducing the lifetime of the material [7]. This property is explained based on the formation of the passive layer on the material surface [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that corrosion is a great problem to be considered in the material design field [5,6]. Pitting corrosion is one of the most critical types of corrosion that leads to undesirable failures reducing the lifetime of the material [7]. Therefore, in order to understand this phenomenon, many studies have been developed to analyse pitting corrosion behaviour of stainless steel [8,9].…”
Section: Introductionmentioning
confidence: 99%